HOW HOBBIES, MUSIC, AND FILMS HELP US (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2025)
This article provides a broad overview of the role and impact of creative activities in human life. It discusses how hobbies contribute to personal development, mental well-being, and social connection. The paper also examines the influence of music and music therapy on the brain, emotion regulation, and cognitive processes, supported by scientific findings. Furthermore, it highlights the advantages of using films in second-language learning, particularly in improving listening, pronunciation, vocabulary acquisition, and learner motivation. The second part of the article critically analyzes the ecological consequences of contemporary land art and artistic interventions in natural environments. Overall, the paper emphasizes both the positive effects of creative activities on human development and the importance of ecological responsibility when interacting with natural ecosystems.